Development of autoimmune hair loss disease alopecia areata is associated with cardiac dysfunction in C3H/HeJ mice. - Eddy Wang; Katy Chong; Mei Yu; Noushin Akhoundsadegh; David J Granville; Jerry Shapiro; Kevin J McElwee (PLoS ONE, 2013)
Alopecia areata (AA) is a chronic autoimmune hair loss disease that affects several million men, women and children worldwide. Previous studies have suggested a link between autoimmunity, stress hormones, and increased cardiovascular disease risk. In the current study, histology, immunohistology, quantitative PCR (qPCR) and ELISAs were used to assess heart health in the C3H/HeJ mouse model for AA and heart tissue response to adrenocorticotropic hormone (ACTH) exposure. Mice with AA exhibited both atrial and ventricular hypertrophy, and increased collagen deposition compared to normal-haired littermates. QPCR revealed significant increases in Il18 (4.6-fold), IL18 receptor-1 (Il18r1; 2.8-fold) and IL18 binding protein (Il18bp; 5.2-fold) in AA hearts. Time course studies revealed a trend towards decreased Il18 in acute AA compared to controls while Il18r1, Il18bp and Casp1 showed similar trends to those of chronic AA affected mice. Immunohistochemistry showed localization of IL18 in chronic AA mouse atria. ELISA indicated cardiac troponin-I (cTnI) was elevated in the serum and significantly increased in AA heart tissue. Cultures of heart atria revealed differential gene expression between AA and control mice in response to ACTH. ACTH treatment induced significant increase in cTnI release into the culture medium in a dose-dependent manner for both AA and control mice. In conclusion, murine AA is associated with structural, biochemical, and gene expression changes consistent with cardiac hypertrophy in response to ACTH exposure.